2021
DOI: 10.1002/jmv.27053
|View full text |Cite
|
Sign up to set email alerts
|

Decreased in‐hospital mortality associated with aspirin administration in hospitalized patients due to severe COVID‐19

Abstract: Hypercoagulability and thrombosis caused by coronavirus disease 2019 (COVID‐19) are related to the higher mortality rate. Because of limited data on the antiplatelet effect, we aimed to evaluate the impact of aspirin add‐on therapy on the outcome of the patients hospitalized due to severe COVID‐19. In this cohort study, patients with a confirmed diagnosis of severe COVID‐19 admitted to Imam Hossein Medical Center, Tehran, Iran from March 2019 to July 2020 were included. Demographics and related clinical data d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 18 publications
4
22
0
1
Order By: Relevance
“…A recent study from Iran assessing 991 patients (336 with prior ASA intake or having started ASA on the first day of hospital admission) demonstrated a significant independent association between ASA and lower in-hospital mortality (RR = 0.75, 95% CI 0.56–0.99) [ 13 ]. Although the study was not carried out with PSM correction, it is worth highlighting the results taking into account that patients with ASA were older and had more comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from Iran assessing 991 patients (336 with prior ASA intake or having started ASA on the first day of hospital admission) demonstrated a significant independent association between ASA and lower in-hospital mortality (RR = 0.75, 95% CI 0.56–0.99) [ 13 ]. Although the study was not carried out with PSM correction, it is worth highlighting the results taking into account that patients with ASA were older and had more comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 14 ] enrolled 24 pairs of patients (after PSM) and reported that among adults (with arterial hypertension and cardiovascular diseases) infected with SARS-CoV-2, low-dose ASA (100 mg/day) was associated with a lower risk of mortality compared with non-ASA users. Among more than 30,000 COVID-19 positive USA Veterans, prior ASA intake was associated with a statistically and clinically significant decrease in overall mortality at 14-days (OR = 0.38, 95% CI 0.32–0.46) and 30-days (OR = 0.38, 95% CI 0.33–0.45) [ 13 ]. One possible interpretation of these results is that ASA is beneficial due to its possible antithrombotic, anti-inflammatory, and immunomodulation effects in community cases of COVID-19, but no longer when patients have a severe condition requiring hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the mortality bene t of aspirin use in patients with COVID-19. (11,12,(17)(18)(19)(20) Nonetheless, the mortality bene t of aspirin was inconsistent among these studies. While some studies observed no signi cant mortality reduction such as the Randomized Evaluation of Covid-19 Therapy (RECOVERY) trial.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study found that aspirin use on admission or within 7-days of admission was associated with decreased mortality in COVID-19 (HR: 0.53) (Chow et al, 2021). Another retrospective study looked at aspirin use either pre-admission (60%) or after admission and found increased mortality in the aspirin group (32% vs. 22%) however, when they controlled for underlying risk factors they found a significant reduction in mortality in patients on aspirin (HR: 0.75) (Aghajani et al, 2021).…”
Section: Targeting Platelets In Covid-19mentioning
confidence: 99%